Dual-Modality Salvage of Recurrent Pacemaker Extrusion in Severe Malnutrition: A Technique Using PTFE Mesh Encapsulation and Fasciocutaneous Flap Coverage - Rani Septrina; Fidi Bhawana Jaya; Euis Maryani (HM Publisher, 2026)
Background: Permanent pacemaker implantation in pediatric patients with severe malnutrition presents a unique surgical challenge due to the absence of a viable subcutaneous protective envelope. In this population, standard device fixation frequently results in recurrent wound dehiscence and device extrusion, often necessitating lead abandonment or epicardial placement. This study evaluates the efficacy of a dual-modality salvage technique integrating a Polytetrafluoroethylene (PTFE) mesh barrier with vascularized fasciocutaneous tissue coverage. Case presentation: We present the case of a 3-year-old male with congenital complete atrioventricular block and severe acute malnutrition, defined by a Weight-for-Height Z-score of less than -3 SD. The clinical course was complicated by three consecutive implant failures over an 8-month period, including two thoracic and one abdominal extrusion, characterized by aseptic pressure necrosis. To salvage the cardiac hardware, a novel sealed-device technique was employed. The pulse generator was encapsulated in a non-absorbable PTFE mesh to minimize the coefficient of friction and placed in a sub-fascial plane. Simultaneously, a random-pattern fasciocutaneous rotation flap was harvested to provide robust, vascularized coverage. Biochemical analysis revealed severe hypoalbuminemia (2.1 g/dL) and anemia pre-operatively. Conclusion: At the 12-month follow-up, the surgical site demonstrated complete physiological integrity with no recurrence of erosion, seroma, or infection. The combination of PTFE encapsulation to mitigate mechanical shearing forces and a fasciocutaneous flap to restore perfusion offers a durable salvage strategy for refractory device extrusion in cachectic pediatric patients.